The Influence Of Internal Control Practices On The Accountability Practices Of A Waqf Institution: A Case Of Al-Rahma International - Mohammed M. Ahmed Ayedh
Internal control practices apply several mechanisms to discharge accountability by ensuring and assessing the organisational financial regulatory compliance process. This study explores the internal control practices in the Al-Rahma International Waqf Institution and examines the role of these internal control practices in enhancing accountability. The study population is the employees of Al-Rahma International in Kuwait and other branches outside Kuwait. The sample comprises 342 employees in Al-Rahma International. A survey questionnaire was used to gather data, where all the data was collected from the respondents at the same time. The analyses of the respondents were conducted using exploratory factor analysis and multiple regression analysis in SPSS. The findings show the regression analysis of both enter and stepwise method that monitoring internal control (ICM) has a significant impact on performance accountability practices. The information and communication internal control (ICI) have a significant impact on the evaluation accountability practices. The results indicate that the practices of internal controls in Al-Rahma are implemented with efficiency and high ethics. The findings indicate that the practices of the accountability in Al-Rahma are virtuous and implemented with high ethics and efficiency. Accountability in Al-Rahma has been developed by taking several procedures to enhance the practices of the accountability inside and outside Al-Rahma. The analysis and findings of the data collected through this research should be of great interest to Al-Rahma International and their donors. Several suggestions are highlighted for improvement based on the results